CONTRIBUTION OF MUALLIM AL KHUDRI BIN KHATIB SHAHIH IN ISLAMIC EDUCATION IN SUBULUSSALAM CITY - Subhani, Subhani; OK, Azizah Hanum; Al Farabi, Mohammad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This research aims to describe the biography of Muallim Al Khudri bin Khatib Shahih, analyze his role in the development of Islamic education in the City of Subulussalam, and analyze the implications of his contributions to Islamic education in the City of Subulussalam. The research method used is a qualitative method with a figure study approach, which is implemented through data collection techniques such as interviews, observation, and analysis of the figure's life journey records. The results showed that Muallim Al Khudri, with an educational background in traditional Islamic boarding schools (dayah) and higher education, has a high dedication to advancing Islamic education in the City of Subulussalam. His role is reflected in the establishment of the Raudhatul Jannah Integrated Islamic Boarding School (ErJe) which implements an integrated Tarbiyatul Muallimin Al Islamiyah (TMI) curriculum, combining religious knowledge, general knowledge, and foreign language skills. He is also active in teaching at Islamic elementary schools (TPA), conducting religious studies, and preaching. The implications of his contributions include increasing the accessibility and quality of Islamic education, strengthening the character and morals of the community, and increasing religious awareness. This research provides a comprehensive picture of the contribution of Muallim Al Khudri in building Islamic education in the City of Subulussalam, as well as its implications for society.